Thematic and Rhematic Progression in Scientific Writing: A Pilot Study - Alvin Ping Leong (Universitas Sanata Dharma, 2022)
The Hallidayan Theme-Rheme framework is commonly used to account for the message structure of language. Much has been done to investigate the message structure of different text types using the Hallidayan framework and Daneš’s notion of thematic progression (TP). Similar studies targeting scientific research articles, however, are few, and the Rhemes in these studies are almost always sidelined. Diagrams capturing the development patterns of Themes and Rhemes at the whole-text level are also lacking. To address these gaps, this study compared the TP and rhematic progression (RP) patterns of 50 scientific research articles, adopting both a diagrammatic and quantitative approach. The quantification of TP and RP was based on the thematic-density index (TDI) and rhematic-density index (RDI), respectively. The results revealed that TDI was greater than RDI at all levels of the text. The TP and RP patterns were also different and distinct. Whereas the TP pattern comprised a simple-linear progression in the introduction section followed by a constant development in the rest of the article, the RP pattern was generally simple-linear in its shape. The observed TP and RP patterns capture not merely the message structure of scientific writing, but its communicative function. Further work involving more varied scientific texts is recommended to investigate whether these patterns are robust across disciplines.